1994
DOI: 10.1023/a:1018933925707
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Antimicrobial treatment failures in children with acute otitis media and concomitant viral respiratory tract infection prompted us to study the effects of influenza A virus infection on middle ear antimicrobial drug penetration. Using a chinchilla model of Streptococcus pneumoniae we compared middle ear elimination rates in 4 groups of chinchillas: (1) control, (2) influenza A virus inoculation alone intranasally, (3) both influenza A and S. pneumoniae inoculation directly into the middle ear, and (4) S. pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Influenza A virus (IAV), coronavirus NL63 and respiratory syncytial virus (RSV) augment bacterial adherence to epithelial cells [1719]; IAV has also been shown to promote nasopharyngeal colonization of S. pneumoniae [20]. Viruses also modify host immune functions [21, 22], and interfere with antibiotic activity [2325]. Viruses alter mucous property and diminish the normal mucociliary clearance of the coating epithelial cells by reducing the production of bactericidal substances in the nasopharynx, ET, and the middle ear cavity, and hence increase bacterial pathogenicity [26, 27].…”
Section: Pathogenesis Of Virus-induced Acute Otitis Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza A virus (IAV), coronavirus NL63 and respiratory syncytial virus (RSV) augment bacterial adherence to epithelial cells [1719]; IAV has also been shown to promote nasopharyngeal colonization of S. pneumoniae [20]. Viruses also modify host immune functions [21, 22], and interfere with antibiotic activity [2325]. Viruses alter mucous property and diminish the normal mucociliary clearance of the coating epithelial cells by reducing the production of bactericidal substances in the nasopharynx, ET, and the middle ear cavity, and hence increase bacterial pathogenicity [26, 27].…”
Section: Pathogenesis Of Virus-induced Acute Otitis Mediamentioning
confidence: 99%
“…If the virus infects the middle ear along with bacteria or viral URI is still ongoing at the time of AOM diagnosis, many earlier studies have shown that viral–bacterial interaction can lead to adverse AOM outcome. Prolonged AOM symptoms and bacteriologic failure result from concurrent viral infections [6, 74, 75], through mechanisms such as virus-induced inflammation [76, 77] and interference of antibiotic penetration into the middle ear [23, 24]. These earlier studies detected viruses by the conventional diagnostics (viral culture and antigen detection), which are less sensitive than molecular diagnostics such as PCR and, therefore, detected viruses only in cases with larger inoculums.…”
Section: Effects Of Viral–bacterial Interactions On Clinical Course Amentioning
confidence: 99%
“…In MEF from children with AOM, concentrations of interleukin-8, histamine and leukotriene B4, have been found to be higher in MEF containing both bacteria and virus, than in MEF containing bacteria or virus alone (8, 9). Another explanation related to the ability of the viruses to induce local inflammation and immunologic reactions that interfere with penetration of antibiotic or dilute antibiotic concentration in the MEF; evidence to support these observations come from both data obtained in chinchilla experiments and in children with AOM (10, 11). …”
Section: Introductionmentioning
confidence: 99%
“…The course of othopathogen-dependent OM involves bacterial colonization on the ME epithelium (Hendrixson and St Geme, 1998;Thornton et al, 2011). Bacterial infection in the ME usually occurs as a secondary infection to viral infection in the nasopharynx that subsequently progresses to ME via the Eustachian tube (Jossart et al, 1994;Jiang et al, 1999) (Figure 1). According to general guidelines in various countries, antimicrobial agents, depending on the age group of children are the treatment of choice of OM.…”
Section: Introductionmentioning
confidence: 99%